Diagnosis dan Tata Laksana Retinoblastoma: Tinjauan Pustaka - Firdausi, Khadijah Nur Al (Cermin Dunia Kedokteran, 2026)
Retinoblastoma is a malignant tumor that originates from the inner nuclear layer of the retina. High morbidity and mortality are caused by late diagnosis. There are two genetic types of retinoblastoma. The first type is hereditary, also known as germline, while the second type is non-hereditary, also known as sporadic or somatic. Tumor classification and staging are important to know because they are key factors in determining prognosis and influence long-term visual function following systemic chemotherapy and focal therapy. International collaboration has developed the International Classification of Retinoblastoma (intraocular tumors). Management aims to save lives and prevent tumor spread, followed by eye preservation and optimization of visual function. Treatment options for retinoblastoma are based on the international classification of intraocular retinoblastoma, the presence or absence of extraocular clinical factors, germline test results, the family’s psychosocial situation, and healthcare facility resources. Early detection of tumors, prevention of metastasis, and appropriate management can maintain globe preservation and optimize vision. If detected early and treated appropriately, the survival rate can be nearly 100%.